Residual effects of static stretching and self-myofascial-release exercises on flexibility and lower body explosive strength in well-trained combat athletes - Sagiroglu, I.; Kurt, C.; Pekünlü, E.; Özsu, I. (Isokinetics and Exercise Science, 2017)
BACKGROUND: The self-myofascial technique is a new exercise modality that is thought to improve muscular performance and restore soft tissue. However, there are limited empirical data demonstrating the efficacy of this technique on athletic performance. OBJECTIVE: The purpose of this study was to determine the effects of self-myofascial-releasing exercises on the residual characteristics of the sit and reach (S&R) and countermovement jump (CMJ) performance in well-trained combat athletes. METHODS: Sixteen well-trained male combat athletes (age: 23.9 ± 3.6 years, mass: 78.78 ± 10.41 kg, combat experience: 12.87 ± 5.23 years) performed three exercise sessions called ``aerobic running (AR)'', ``aerobic running combined with static stretching (AR + SS)'', and ``aerobic running combined with self-myofascial release (AR + SMR)'' at 48 hour intervals in a randomized crossover design. After each session, the subjects performed the S&R and CMJ tests successively with 30-s of rest between the tests at the 15th second and at the 2nd , 4th , 6th , 8th , 10th , 15th , and 30th minute during the recovery period. RESULTS: ANOVA and the post-hoc LSD (Least Significant Difference) test revealed that the AR + SMR treatment increased the flexibility greater than AR + SS (p= 0.029) at the 45th second. Additionally, the AR + SMR treatment resulted in less of a decrease in CMJ height compared to AR + SS at the 10th minute (p= 0.025). A larger decrease in the CMJ height was found after AR + SS compared to the AR and AR + SMR treatments at the 10th and 15th minute, respectively (p= 0.025 and p= 0.038). These results revealed that SMR had no advantage over AR and SS in terms of enhancing flexibility. A statistically insignificant inhibitory effect of SMR was detected on the CMJ performance. SS appeared to have an inhibitory effect on the CMJ performance for approximately 15 minutes. CONCLUSION: SMR may have a detrimental effect on CMJ performance. Trainers or athletes should consider using the SMR technique before training or competition to prevent possible power decrement. ABSTRACT FROM AUTHOR